Capacity Building Dinas Sosial Dalam Penanggulangan Kemiskinan Ekstrem di Kabupaten Karawang - Arsiyana Widy Pratama; Rachmat Hidayat; Ani Nurdiani Azizah (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to find out and examine the Cappacity Building of the Social Service in Reducing Extreme Poverty in Karawang Regency by using the Gandara theory in Bambang Irawan (Organizational Capacity and Public Service, 2016) in which there are dimensions of capacity building covering five dimensions, namely (1) Preparation, (2) Analysis, (3) Planning, (4) Implementation, (5) Evaluation. This study used descriptive qualitative method. The data collection technique was carried out through triangulation which included interviews, observations and documentation studies, then the data that had been obtained were analyzed through three stages, namely data reduction, data presentation and conclusion drawing. The results of research and discussion show that it is still not optimal in all dimensions of the Social Service Cappacity Building variable in reducing extreme poverty in Karawang Regency where preparations are still immature so they are not able to take advantage of opportunities from natural and industrial potential, the analysis is not sharp enough to cause poor planning. not very good, which causes the percentage of the extreme poor in Karawang to be higher than the average for the province of West Java. Implementation is carried out through several assistance programs not towards community empowerment so that the Social Service is required to be able to carry out a large-scale evaluation in order to optimize the prevention of extreme poverty in Karawang Regency.